A continuous flow microfluidic device based on contactless dielectrophoresis for bioparticles enrichment. Issue 3 (25th September 2017) - Rahmani, Ali; Mohammadi, Aliasghar; Kalhor, Hamid Reza
Abstract: In recent years, applications of dielectrophoresis‐based platforms have been recognized as effective and dependable approach to separate cells and bioparticles, suspended in different carrier fluids, based on particle size and electrical properties. In this study, a microfluidic device was fabricated by an unprecedented electrode pattern, and several experiments were performed to enrich samples including either of yeast, Escherichia coli, or latex particles. A chemical deposition‐based method was employed for fabrication of microelectrodes, inducing nonuniform electric field required for dielectrophoresis‐based separation. One major advantage of our employed method is low fabrication cost, in addition to its accuracy and operation at low voltages. The performance of the microfluidic device in enriching either of injected samples was studied using spectrophotometric techniques. The effects of experimentally controllable parameters (applied‐voltage amplitude and frequency, and flow rate) were studied by changing a parameter while keeping the others constant. It became evident that all the aforementioned parameters had modulating impact on the performance of the microfluidic device. Furthermore, to investigate binary interactions among the parameters, response surface methodology was exploited, resulting in a second‐order polynomial model for the performance of the device as a function of the parameters. The model was employed for finding the optimum values of the parameters at which the performance of the device is the highest. At optimum values for the experimentally controllable parameters, enrichment efficiencies of 87 ± 2, 82 ± 4, and 86 ± 3% for, respectively, yeast, E. coli, and latex particles were obtained experimentally, confirming the ability of the proposed method for biological and polymeric particles enrichment.